2005
DOI: 10.1007/s11104-005-8699-2
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to the Potential of Transgenic Trifolium subterraneum L. Plants that Exude Phytase when Grown in Soils with a Range of Organic P Content

Abstract: Growth and P-nutrition of transgenic Trifolium subterraneum L. which express a chimeric fungal phytase gene (ex::phyA) was compared to azygous and wild-type controls in a range of soils that differed in organic P content. Shoot and root growth by plant lines were measured and effects of reducing the influence of soil microorganisms were investigated by pasteurising the soils. Plants that expressed phyA did not have better P-nutrition than control plants after 56 days growth, except in a soil that contained a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…7). These results support the hypothesis that the solubility of organic P is a limiting factor for mobilization in the soil, as inferred from results of other studies (George et al 2005a;Wasaki et al 2009). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…7). These results support the hypothesis that the solubility of organic P is a limiting factor for mobilization in the soil, as inferred from results of other studies (George et al 2005a;Wasaki et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…For effective use of these forms, chelation by organic acids is important (George et al 2005a;Wasaki et al 2009). Adams and Pate (1992) reported that white lupin plants can use phytate-P in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Plants genetically modified to release an extracellular fungal phytase (from Aspergillus niger) from roots showed similar novel ability to acquire P directly from phytate . However, when evaluated in soil, these plants show significant improvement in P nutrition only in soils with higher substrate levels (as measured by enzyme lability assays), or in soils that were artificially amended with phytate (George et al, 2005a(George et al, , 2005b. In addition to the importance of substrate availability, rapid adsorption of phytase to the soil solid phase was observed with loss of activity being dependent both on enzyme characteristics and soil properties (George et al, 2007a;Giaveno et al, 2010).…”
Section: Mineralization Of Organic Pmentioning
confidence: 99%
“…Genetic manipulation of plants and microorganisms for key traits that are known to be associated with P mobilization or growth promotion (e.g. extracellular phytase and genes for synthesis and/or release of organic anions by plants and microorganisms; Gyaneshwar et al, 2002;George et al, 2005a;Rodriguez et al, 2006), along with generation of specific mutants in key target genes for particular traits (e.g. organic anion release in Pseudomonas spp., Miller et al, 2010), are useful for both elucidation of mechanisms and for quantifying their contribution to increased P availability in soil.…”
Section: Ecological Considerations and Future Prospectsmentioning
confidence: 99%
“…Transgenic Trifolium subterraneum transformed with a phytase gene from Aspergillus niger improved P uptake of plants supplied with phytate and grown in agar under sterile conditions (Richardson et al 2001), but this positive effect was not seen in soil grown plants, possibly because phytate was bound to soil particles and therefore not available (George et al 2005). Delhaize et al (2001) overexpressed a citrate synthase gene from Pseudomonas aeruginosa in tobacco (Nicotiana tabacum L.) and detected greatly enhanced citrate synthase protein levels in the transgenic plants.…”
Section: Introduction Of New Traits and Genes Through Genetic Modificmentioning
confidence: 99%